Modeling of Split Ring Resonator for Harvesting Electromagnetic Energy with Resonant Frequency of 950 MHz (Universitas Ahmad Dahlan, 2022)
The use of a split ring resonator (SRR) as an electromagnetic energy harvester can increase the flexibility of electronic devices because the rechargeable power does not require the connection of cables and batteries. The energy used in the electromagnetic 950 MHz implies one of the frequencies of the wireless network en masse in the room. The objection in this research is to find out how to design an SRR that has a resonant frequency of around 950 MHz, and how to know its characteristics. Based on previous research, variations were carried out with three measurement parameters which were carried out separately and simulated using CST software to achieve a resonant frequency of 950 MHz. The results of the simulation and design process with CST software are three SRR models which are then named SRR 1, SRR 2, and SRR 3. SRR 1 has a ring width 5.6 mm,a slit width 2.7 mm, a ringside length 35 mm, and a ring plate thickness 0.017 mm. SRR 2 has 2.9 mm in a ring width, 10.8 mm in a slit width, 35 mm in a ringside length, and 0.017 mm in a ring plate thickness. SRR 3 has a ring width 2.9 mm, a slit width of 2.7 mm, a ringside length of 32.25 mm, and a ring plate thickness of 0.017 mm. SRR is expected to obtain energy from wireless network energy that is often used indoors.